Astronomical Observing Conditions at Xinglong Observatory from 2007 to 2014. (4th January 2016) - Zhang, Ji-Cheng; Ge, Liang; Lu, Xiao-Meng; Cao, Zi-Huang; Chen, Xu; Mao, Yong-Na; Jiang, Xiao-Jun
Abstract: Xinglong Observatory of the National Astronomical Observatories, Chinese Academy of Sciences (NAOC), is one of the major optical observatories in China, which hosts nine optical telescopes including the Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST) and the 2.16 m reflector. Scientific research from these telescopes is focused on stars, galaxies, and exoplanets using multicolor photometry and spectroscopic observations. Therefore, it is important to provide the observing conditions of the site, in detail, to the astronomers for an efficient use of these facilities. In this article, we present the characterization of observing conditions at Xinglong Observatory based on the monitoring of meteorology, seeing and sky brightness during the period from 2007 to 2014. Meteorological data were collected from a commercial Automatic Weather Station (AWS), calibrated by China Meteorological Administration. Mean and median wind speed are almost constant during the period analyzed and ranged from 1.0 to 3.5 m s -1 . However, high wind speed (≥15 m s -1 ) interrupts observations, mainly, during the winter and spring. Statistical analysis of air temperature showed the temperature difference between daytime and nighttime, which can be solved by opening the ventilation device and the slit of the dome at least 1 hr before observations. Analysis resulted in average percentage of photometric nights and spectroscopic nights are 32% and 63% per year, respectively. The distribution of photometric nights and spectroscopic nights has a significant seasonal tendency, worse in summer due to clouds, dust, and high humidity. Seeing measurements were obtained using the Differential Image Motion Monitor (DIMM). Mean and median values of seeing over 1 year are around 1.9″ and 1.7″, respectively. Eighty percent of nights with seeing values are below 2.6″, whereas the distribution peaks around 1.8″. The measurements of sky brightness are acquired from the Sky Quality Meter (SQM) and photometric observations. Analysis shows that sky brightness at the zenith is around 21.1 mag arcsec -2 and becomes brighter with a larger zenith angle. Sky brightness increases due to the light pollution of the surrounding cities, Beijing, Tangshan, and Chengde. Significant influence toward the direction of Beijing, at an altitude of 30°, can increase the sky brightness up to 20.0 mag arcsec -2 . Sky brightness reduces after midnight, mainly because of the influence of city lights and the artificial acts. The above results suggest that Xinglong Observatory is still a good site for astronomical observations. Our analysis of the observing conditions at Xinglong Observatory can be used as a reference to the observers on targets selection, observing strategy, and telescope operation.